Developing core economic outcome sets for asthma studies: a protocol for a systematic review. Issue 8 (11th August 2017) - Hounsome, Natalia; Fitzsimmons, Deborah; Phillips, Ceri; Patel, Anita
Abstract : Introduction: Core outcome sets are standardised lists of outcomes, which should be measured and reported in all clinical studies of a specific condition. This study aims to develop core outcome sets for economic evaluations in asthma studies. Economic outcomes include items such as costs, resource use or quality-adjusted life years. The starting point in developing core outcome sets will be conducting a systematic literature review to establish a preliminary list of reporting items to be considered for inclusion in the core outcome set. Methods and analysis: We will conduct literature searches of peer-reviewed studies published from January 1990 to January 2017. These will include any comparative or observational studies (including economic models) and systematic reviews reporting economic outcomes. All identified economic outcomes will be tabulated together with the major study characteristics, such as population, study design, the nature and intensity of the intervention, mode of data collection and instrument(s) used to derive an outcome. We will undertake a 'realist synthesis review' to analyse the identified economic outcomes. The outcomes will be summarised in the context of evaluation perspectives, types of economic evaluation and methodological approaches. Parallel to undertaking a systematic review, we will conduct semistructured interviews with stakeholders (including people with personal experience of asthma, health professionals, researchers and decision makers) in order to explore additional outcomes which have not been considered, or used, in published studies. The list of outcomes generated from the systematic review and interviews with stakeholders will form the basis of a Delphi survey to refine the identified outcomes into a core outcome set. Ethics and dissemination: The review will not involve access to individual-level data. Findings from our systematic review will be communicated to a broad range of stakeholders including clinical guideline developers, research funders, trial registries, ethics committees and other regulators.